2015
DOI: 10.25148/crcp.3.1.16092135
|View full text |Cite
|
Sign up to set email alerts
|

Is the Corporate Elite Fractured, or is there Continuing Corporate Dominance? Two Contrasting Views

Abstract: This article compares two recent analyses of continuity and change in the American power structure since 1900, with a main focus on the years after World War II. The first analysis asserts that the "corporate elite" has fractured and fragmented in recent decades and no longer has the unity to have a collective impact on public policy. The second analysis claims that corporate leaders remain united, albeit with moderate-conservative and ultra-conservative differences on several issues, and continue to have a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 100 publications
4
16
0
Order By: Relevance
“…The empirical study of capital ownership structure is based on Domhoff's membership network analysis, [58][59][60][61][62] identifying membership in networks which begins with a search for connections among the organizations that are thought to constitute the dominant group. After that, it is necessary to study other types of links such as kinship ties or flows of information between organizations (one of the most important of these types of links is about the size and direction of money flows in the network).…”
Section: Research Design and Case Studymentioning
confidence: 99%
“…The empirical study of capital ownership structure is based on Domhoff's membership network analysis, [58][59][60][61][62] identifying membership in networks which begins with a search for connections among the organizations that are thought to constitute the dominant group. After that, it is necessary to study other types of links such as kinship ties or flows of information between organizations (one of the most important of these types of links is about the size and direction of money flows in the network).…”
Section: Research Design and Case Studymentioning
confidence: 99%
“…Elite political consensus also continues to reflect elites' positions in prominent policy-planning organizations, such as the Business Roundtable and U.S. Chamber of Commerce (Banerjee and Burroway 2015). In fact, Domhoff (2015) argues that the policy-planning network is more important than board interlocks for securing elite political consensus.…”
Section: Board Fracturing and Corporate Short-termismmentioning
confidence: 99%
“…We also find that elite cohesion mitigates pressures to cut R&D (β=-.03, p<.05) and to increase ERRs (β=.02, p<.05) when the firm is at risk of missing analysts' earnings projections. Finally, we find that the elite cohesion effects are most pronounced when the network's overall structure is more cohesive.For our second set of robustness tests, prior research has found that policy-planning organizations, such as the Business Roundtable and U.S. Chamber of Commerce, are important sources of elite cohesion in political and policy interests(Banerjee and Burroway 2015;Burris 2008;Domhoff 2015). To our knowledge, no prior study has explored whether these alternative sources of elite cohesion substitute for board interlocks in firm-level strategy and corporategovernance outcomes (but seeCarroll and Carson 2003).…”
mentioning
confidence: 99%
“…In fact, between 1973 and 1995, which is the exact time frame of the fracturing of the interlock network (Mizruchi, 2013), the share of corporate network density (i.e., how connected corporations are to each other) that policy planning organizations are responsible for increased by over 200%. Although the PPN may have, as Domhoff (2015) argues, always been a center of corporate class-wide power, we lack the data to test this claim. Regardless of the importance of the PPN in the past, however, it is eminently plausible, given the expansion since the 1970s, that as banks abandoned the center of intercorporate network and its contribution to cohesion declined, the PPN has remained as the corporate network holding together the corporate elite.…”
Section: The Policy Planning Networkmentioning
confidence: 99%
“…In this article, we will argue that the corporate elite do have a different enclave, but it is not hidden from public scrutiny-it is the giant institutional apparatus of policy discussion groups, think tanks, and corporate foundations that make up what Domhoff (2014;2015) refers to as the policy planning network (PPN). That is, we will argue that the fractured elite thesis overlooks two factors that counteract the decline of the domestic interlock network-a growing PPN and a stable inner circle.…”
Section: Introductionmentioning
confidence: 99%